2015
DOI: 10.1515/jppr-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of: the pea aphid, Acyrthosiphon pisum (Harris), its natural enemies the seven spotted lady beetle Coccinella septempunctata Linnaeus and variegated lady beetle Hippodamia variegata Goeze, and their parasitoid Dinocampus coccinellae (Schrank)

Abstract: Abstract:Two important lady beetle species commonly found in alfalfa fields in Iran are the variegated lady beetle Hippodamia variegata Goeze and the seven spotted lady beetle Coccinella septempunctata (Linnaeus, 1758) (Coleoptera: Coccinellidae). These two species attack many aphid species including the pea aphid, Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae). In this study, the seasonal population changes of A. pisum, H. variegata, C. septempunctata and the parasitoid, Dinocampus coccinellae (Schrank) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The use of predator of aphid and mite as one of the component of the module M II also leads to reduction of these pests. It has been shown that Coccinellid beetle have a major role in reducing the pea aphid populations in alfalfa fields that was conducted in Hamedan, Iran (Soleimani and Hossein, 2015). The findings of Jakhar and Chaudhary (2013) 2).…”
Section: Resultsmentioning
confidence: 94%
“…The use of predator of aphid and mite as one of the component of the module M II also leads to reduction of these pests. It has been shown that Coccinellid beetle have a major role in reducing the pea aphid populations in alfalfa fields that was conducted in Hamedan, Iran (Soleimani and Hossein, 2015). The findings of Jakhar and Chaudhary (2013) 2).…”
Section: Resultsmentioning
confidence: 94%
“…Many aphidophagous ladybird beetles (Coleoptera: Coccinellidae) are known to be exploited for conservative or augmentative release biocontrol programs of several economically important aphids in diverse crops, outdoors and in greenhouses 2 , suppressing aphid infestations below economically damaging levels 36 . Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) is a generalist predator, is geographically wide-spread 37 , and has been extensively employed as a biocontrol agent of soft-bodied insects, including aphids in a diversity of crops 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Multivoltine parasitoid species, such as D. coccinellae, must synchronize their active period with that of their hosts (16), whose availability in turn depends on that of the host's prey. As a result of this and other factors, levels of parasitism may also vary over the course of a growing season (115,138,150). Host dissections showed that, in the field, parasitism rates of H. axyridis and Coleomegilla maculata, a native ladybird species in North America, were similar (67), but due to reduced host suitability, the rate of emergence of adult parasitoids from the former species is much lower (42).…”
Section: Interaction Between Ladybird Beetles and Dinocampus Coccinellaementioning
confidence: 99%